Protection Mechanisms and Revitalization Strategies for Industrial Heritage - Wu, Yifan; Zhen, Ling; You, Weifeng (International Journal of Social Sciences and Public Administration, 2024)
Industrial heritage is a product of the Industrial Revolution and an important asset for a country or region. The protection and revitalization of industrial heritage have become pressing tasks in the present era. In the new era, it is essential, on the one hand, to establish a comprehensive and scientific policy system for industrial heritage protection by creating specialized protection agencies and ensuring strong governmental support. On the other hand, revitalization strategies should be developed based on practical needs, such as transforming industrial heritage into cultural and art centers, converting it into creative industry parks, and integrating industrial heritage resources into tourism and leisure industries. These strategies aim to ensure the comprehensive protection and sustainable use of industrial heritage.